2009
DOI: 10.1021/es901274s
|View full text |Cite
|
Sign up to set email alerts
|

Redox Transformation of Arsenic by Fe(II)-Activated Goethite (α-FeOOH)

Abstract: The redox state and speciation of the metalloid arsenic (As) determine its environmental fate and toxicity. Knowledge about biogeochemical processes influencing arsenic redox state is therefore necessary to understand and predict its environmental behavior. Here we quantified arsenic redox changes by pH-neutral goethite [alpha-Fe(III)OOH] mineral suspensions amended with Fe(II) using wet-chemical and synchrotron X-ray absorption (XANES) analysis. Goethite itself did not oxidize As(III) and, in contrast to ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
236
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(270 citation statements)
references
References 52 publications
31
236
2
1
Order By: Relevance
“…During data collection, As samples were maintained at a temperature of 5 K to prevent beam-induced redox reactions using an Oxford Instruments CF1208 continuous flow liquid helium cryostat (Oxford Instruments, Abingdon, UK). [58] Energy selection was accomplished with a Si (220) monochromator. All Fe EXAFS spectra were collected in fluorescence mode with a wide-angle collection ionisation chamber (Lytle detector).…”
Section: X-ray Absorption Spectroscopy (Xas)mentioning
confidence: 99%
See 2 more Smart Citations
“…During data collection, As samples were maintained at a temperature of 5 K to prevent beam-induced redox reactions using an Oxford Instruments CF1208 continuous flow liquid helium cryostat (Oxford Instruments, Abingdon, UK). [58] Energy selection was accomplished with a Si (220) monochromator. All Fe EXAFS spectra were collected in fluorescence mode with a wide-angle collection ionisation chamber (Lytle detector).…”
Section: X-ray Absorption Spectroscopy (Xas)mentioning
confidence: 99%
“…[59] Uranium reference compounds included uranyl acetate and uraninite. [60] Arsenic reference compounds included As III adsorbed to goethite, As V adsorbed to goethite [58] and orpiment (As 2 S 3 ). Standards of arsenic adsorbed to goethite were prepared according to Amstaetter et al by adding 1.2 mg L À1 of sodium arsenite and sodium arsenate to a 5.4 g L À1 suspension of goethite (Bayferrox 920 Z, LANXESS Deutschland GmbH, Leverkusen, Germany).…”
Section: X-ray Absorption Spectroscopy (Xas)mentioning
confidence: 99%
See 1 more Smart Citation
“…Green rust was formed under anaerobic conditions with ferrous added. Some part of green rust could transform to goethite after oxidation (Amstaetter et al 2010). Part of hematite could dissolve in WA at first, then the Fe 3?…”
Section: Chemical Fractionation Of Arsenic Using Sequential Extractionsmentioning
confidence: 99%
“…Iron(hydr) oxides could only slightly oxidize As(III), when they were induced or catalyzed, for example, by Fe(II) or light. Early studies showed the rapid oxidation of As(III) to As(V) at the surface of goethite, magnetite and ferrihydrite in Fe(II)-mediated reactions (Amstaetter et al, 2010;Ona-Nguema et al, 2010). It is reported that goethite interacting with dissolved Fe(II) produced the highest redox activity compared with other Fe(III) (oxy)hydroxides (Elsner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%